Light-based therapies and radiodermatitis - Talita Oliveira de Lima; Karina Alexandra Batista da Silva Freitas; Karen Aline Batista da Silva; Maria Fernanda Setúbal Destro Rodrigues; Thais Barbosa dos Santos; Illora Aswinkumar Darbar Shimozato; Christiane Pavani; Rebeca Boltes Cecatto (EXCLI Journal : Experimental and Clinical Sciences)
The main treatments for cancer are radiotherapy and chemotherapy, but they can generate side effects such as fatigue, myelosuppression, and radiodermatitis. The Multinational Association of Supportive Care in Cancer already recommends the use of laser for radiodermatitis in breast cancer patients. However, in relation to head and neck cancer patients, there is a lack of studies clearly demonstrating clinical effects and identifying the best light parameters for the treatment of radiodermatitis. This study reports on three oncological patients with radiodermatitis treated with light-based therapies to show clinical improvements in lesion grades and to discuss the effects of laser and its parameters. A retrospective report of three head and neck cancer patients with radiodermatitis, treated with photobiomodulation and photodynamic therapy at an outpatient health clinical facility. The Visual Analog Scale, Toxicity Criteria of the Radiation Therapy Oncology Group (RTOG) Scale, and the clinical characteristics of lesions were evaluated before and after a photobiomodulation plus photodynamic therapy protocol. Improvements were observed in cases with RTOG grade III with just 4 treatment sessions required for complete healing of the lesions. The patient with RTOG grade IV required antibiotic therapy, temporary suspension of radiotherapy, and more than 4 light sessions to achieve improvements. None of the patients showed worsening of the lesions, necrosis, or infection after treatment with no adverse effects. Head and neck cancer patients with radiodermatitis treated with phototherapy obtained good results in wound healing and pain relief in a short period. These case reports embody the easy-to-apply implementation of a light protocol in a health facility based on previous scientific evidence with positive results and no short-term side effects. In light of the negative impact on quality of life caused by radiodermatitis, health teams should be encouraged to design research study protocols involving light-based therapies.